THE USE OF DEIXIS IN ENGLISH TRANSLATION OF AL-QURAN IN THE CHAPTER 30 (JUZ 'AMMA) - DEWI , ONA KURNIANING (2007)
This research is about the use of deixis in English Translation of Al-qur'an in the Chapter 30. The object of this study is the use of deixis, including the form and reference of deixis. The objectives of this study are (1) to describe the form of deixis used in Juz 'Amma, and (2) to describe the reference of deixis used in Juz 'Amma. This is a descriptive qualitative research, and in collecting the data, the writer employs documentation method by gathering deixis used in English translation of Al-Qur'an in the chapter 30. After that the writer makes classification the data based on the form of deixis and its reference. Finally, she describes the data. The result of the research shows that from 205 data items. It consists of 124 (60,5%) person deixis, which contains 9 items (4,3%) first person deixis, 65 items (31,7%) second person deixis, and 50 items (24,3%) third person deixis; 21 items (10,2%) time deixis contains 9 items (4,3%) covert time deixis, 10 items (5,0%) tense, 2 items (10 %) explicit time deixis; 52 items (25,4%) social deixis are categorized as absolute social deixis; 5 items (2,4%) discourse deixis, and 3 item (1,5 %) place deixis. Then, in analizing the reference, the writer finds fourteen references of deixis in juz 'Amma. They are referring to first person, second person, referring to third person, preceding portion, past time, present time, future time, social relationship, and certain place namely the place of someone when he dies, to the first time of sending Al-qur'an down to Rasulullah; the glory night; and the decree of everything for one year, referring to the time finishing of the night of Al-Qodr, referring to the place of Gabriel, referring to the place where Moses got revelation from Allah, and referring to the Day of the Conquest of Mecca.